Predictive value of DNA methylation in the efficacy of chemotherapy for gastric cancer - Li, Ye; Mo, Ning; Yang, Dong; Lin, QiuLu; Huang, WenFeng; Wang, Rensheng (Frontiers in Oncology, 2023)
Gastric cancer (GC) is one of the most common causes of cancer-related death. Drug resistance in chemotherapy often occurs in patients with GC, leading to tumor recurrence and poor survival. DNA methylation is closely related to the development of cancer. To investigate the role of DNA methylation in chemotherapy resistance in GC patients, we conducted a comprehensive analysis using DNA methylation data and survival information obtained from The Cancer Genome Atlas. Patients receiving adjuvant chemotherapy for GC survived longer. Univariate Cox analysis was performed to screen for differential DNA methylation of chemotherapy response in patients who did and did not receive chemotherapy; 308 differentially methylated genes were demonstrated to be associated with prognosis. Multivariate Cox analysis was then performed to identify the independent prognostic genes, which revealed that when n = 6, the model was the best. The six genes were C6orf222, CCNL1, CREBZF, GCKR, TFCP2, and VIPR2. A prognostic risk model was constructed based on the DNA methylation levels of these six genes: risk score = 0.47123374*C6orf222 + 9.53554803*CCNL1 + 10.40234138* CREBZF + 0.07611856* GCKR + 18.87661557*TFCP2 − 0.46396254* VIPR2. the six newly identified DNA methylated genes proved to form an effective and stable model for predicting the prognosis of GC patients receiving adjuvant therapy, outperforming clinicopathological features. The clinical application of the six DNA methylated gene signature will assist in risk classification to guide personalized treatment of GC patients. Despite lacking systematic experimental validation, our study provides a basis for DNA methylation modules as a clinical tool for prognostic assessment after adjuvant chemotherapy. The six DNA methylated gene signature may also provide potential therapeutic targets for the treatment of drug resistance in GC patients.